Study of periodic and optical controlled structures for microwave circuits - Xu, Ying (2009)
Periodic structures have found wide applications in modern communication systems such as filters, power combiners and radar systems. Nowadays, periodic structures play an important role in wireless communication systems due to their attractive features such as compact size, ease of fabrication and high efficiency. However,with the rapid progress of technology, higher requirements have risen which require the devices have more compact size, lighter weight and multi-function to accommodate various services. The sizes and the weight of periodic structures can be reduced by applying novel split ring patterned photonic bandgap/electromagnetic (PBG/EBG) structures to one dimensional microstrip line. These bandgap structures realized on semiconductor material could be exploited for optically controlled behavior. These kinds of periodic structure and their applications are the main subjects of study in this thesis. Periodic aperture patterns etched on the ground plane of a microstrip line have been extensively investigated by many researchers. However, recently few research works have been reported on split ring pattern photonic bandgap structures and optical controlled photonic bandgap structures. In this thesis, a thorough study has been conducted on the scattering and circuit perspectives, radiation efficiency and mutual coupling of these periodic structures have been estimated.